2016
DOI: 10.1596/1813-9450-7571
|View full text |Cite
|
Sign up to set email alerts
|

Egypt: Guiding Reform of Energy Subsidies Long-Term

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In this context, the IMF has estimated that the energy subsidy in the Middle East region stood at $237 billion in 2011, which represented 48% of the total subsidy in the world, 8.6% of the gross domestic product (GDP) and 22% of government revenues 3 . These figures are considerably high compared to the world averages, where the subsidy to the GDP and revenue ratios amount to 0.7% and 2.1% respectively, and are particularly acute for oil exporting countries (Griffin et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…In this context, the IMF has estimated that the energy subsidy in the Middle East region stood at $237 billion in 2011, which represented 48% of the total subsidy in the world, 8.6% of the gross domestic product (GDP) and 22% of government revenues 3 . These figures are considerably high compared to the world averages, where the subsidy to the GDP and revenue ratios amount to 0.7% and 2.1% respectively, and are particularly acute for oil exporting countries (Griffin et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…In Egypt, several studies estimated the potential impact of energy subsidy reform. Griffin, Laursen, and Robertson (2016) and Banerjee et al (2017) used dynamic computable general equilibrium (DCGE) models and found that the impact of the energy subsidy cut in July 2014 should lead to only a modest decline in real household consumption and only a slight increase in poverty in the short-term, while resulting in sizeable structural change in the economy and increase in economic growth in the longer term. Since these two studies for Egypt were conducted, the GOE has scaled up its economic reform agenda significantly by floating the exchange rate and by further cutting energy subsidies.…”
Section: Global Experiencementioning
confidence: 99%
“…Applying a price elasticity of electricity (gasoline) consumption equal to -0.33 (-0.21) would lead to an average total direct effect of -1.92 percent, with the bottom quintile experiencing a loss of -2.43 percent. and a previous energy-focused social accounting matrix (SAM) 2010/11 by Griffin et al (2016). Key changes include:…”
Section: An Energy-focused Dynamic Computable General Equilibrium Modmentioning
confidence: 99%
“…Energy subsidies were one of the main causes of this bleak picture. Expenditure on fuel subsidies had grown with a compound annual growth rate of 26 per cent between 2002 and 2013 (Clarke 2014), amounting to about USD 21 billion, which represented 8.5 per cent of GDP (Griffin et al 2016: 2) and 20 per cent of public expenditure (El-Katiri and Fattouh 2015). The July 2014 reforms were steep price increases affecting various consumer groups and nearly all fuels and energy products, with LPG being the one notable exception.…”
Section: A Crisis Of Unprecedented Proportions and The July 2014 Reformsmentioning
confidence: 99%
“…Also, wealthy Egyptians who favoured stability in 2014 are increasingly discontent as they feel the grip of Sisi's policies that generally favour the poor (Walsh 2016). As far as the military is concerned, the 2014 reforms caused a shift in production and investment to the construction sector (Griffin et al 2016). However, not all construction projects have yielded results as fast as hoped.…”
Section: Frustration With the Change Of The Social Contractmentioning
confidence: 99%